As contribuições das metodologias ativas na formação de professores da educação profissional e tecnológica no Instituto Federal do Amapá - SOUZA, Kelly Cristina Barbosa de (2021)
In the context of Professional and Technological Education (PTE), teacher development focused on the use of differentiated teaching methodologies reflects on students' learning and the quality of school education. Therefore, this is a very important topic and, then, requires constant study. Thus, this study is inserted in the line of research Educational Practices in Professional and Technological Education. Specifically, it is located in Macro project 1, which addresses methodological proposals and didactic resources in formal and non-formal teaching spaces at PTE comprising projects that address the main issues of teaching and learning. The general objective of this work was to verify the contributions of active methodologies in the development of PTE teachers at the Amapá Federal Institute of Education, Science and Technology of Amapá (IFAP). The research of this study is characterized as of an applied nature, with a qualitative and quantitative approach and its data collection was done through a semi-structured questionnaire applied to the professors of the Santana and Laranjal do Jari campus. The data analysis consisted of a graphical representation using a histogram based on the information collected in the closed questions and qualitative analysis of the content of the open questions. As it is research with human beings, the project was submitted and approved by the Research Ethics Committee. The results presented by the research showed the need for continuing education for teachers and that the main challenges that permeate the performance of this teacher in PTE are linked to the fact that teachers work at different levels of education and in classes with a large number of students, which is a reality of education in Brazil. Bearing in mind that the research was developed during the SARS-CoV-2 (Covid-19) pandemic period, a time when teachers and students had considerable changes regarding the teaching-learning processes through remote teaching, another aspect evidenced was concerning pedagogical practices and the use of new technologies. From these points, this study culminated in the elaboration of a short course as an Educational Product entitled “Active Methodologies: an alternative to teaching work at PTE”. This was aimed at meeting the demand for continuing education found in the research and encouraging the use of Active Methodologies in classrooms.